2020
DOI: 10.1101/2020.03.04.976274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substrate Specificity of the TRAMP Nuclear Surveillance Complexes

Abstract: During nuclear surveillance in yeast, the RNA exosome functions together with the TRAMP complexes. These include the DEAH-box RNA helicase Mtr4 together with an RNA-binding protein (Air1 or Air2) and a poly(A) polymerase (Trf4 or Trf5). To better determine how RNA substrates are targeted, we analyzed protein and RNA interactions for TRAMP components. Mass spectrometry identified three distinct TRAMP complexes formed in vivo. These complexes preferentially assemble on different classes of transcripts. Unexpecte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…RNA can also be degraded by Rrp6 exonuclease that is located on the top of the exosome. In addition, it has been proposed that RNA can access Dis3 directly without passing through the channel ("direct access", da conformation) (Bonneau et al, 2009;Delan-Forino et al, 2017;Han and van Hoof, 2016;Liu et al, 2014;Makino et al, 2013Makino et al, , 2015. However, the functional contribution of each model as well the mechanisms that direct routing of substrates have remain unexplored.…”
Section: Comparative Ric With Exosome Mutants Reveals Differences In mentioning
confidence: 99%
See 3 more Smart Citations
“…RNA can also be degraded by Rrp6 exonuclease that is located on the top of the exosome. In addition, it has been proposed that RNA can access Dis3 directly without passing through the channel ("direct access", da conformation) (Bonneau et al, 2009;Delan-Forino et al, 2017;Han and van Hoof, 2016;Liu et al, 2014;Makino et al, 2013Makino et al, , 2015. However, the functional contribution of each model as well the mechanisms that direct routing of substrates have remain unexplored.…”
Section: Comparative Ric With Exosome Mutants Reveals Differences In mentioning
confidence: 99%
“…Behaviour of a given protein in the RIC experiment reflects the mean RNA association of this protein in an ensemble of states. It was suggested that in wild-type, the preferred state of the nuclear exosome is the actively channel-threading conformation (Bonneau et al, 2009;Delan-Forino et al, 2017;Schneider et al, 2012). To test this hypothesis, we sought to perturb the system by using defined mutants of the exosome complex.…”
Section: Comparative Ric With Exosome Mutants Reveals Differences In mentioning
confidence: 99%
See 2 more Smart Citations
“…Budding yeast TRAMP includes one of two nontemplated poly(A) polymerases of the Polβ family, Trf4 or Trf5, and one of two zinc-knuckle RNA-binding proteins, Air1 or Air2 (24)(25)(26)(27). TRAMP promotes degradation of RNA transcripts produced by all three RNA polymerases (28) through the addition of short oligo-adenylated tails to the 3′ end of RNAs (24,25,29,30).…”
mentioning
confidence: 99%